Emergency department responses to nursing shortages - Nicole R. Hodgson; Richard Kwun; Chad Gorbatkin; Jeanie Davies; Jonathan Fisher; on behalf of the ACEP Emergency Medicine Practice Committee (International Journal of Emergency Medicine, 2024)
Abstract Background The COVID-19 pandemic exacerbated the nursing shortage, which is predicted to continue to worsen with significant numbers of nurses planning to retire within the next 5 years. There remains a lack of published information regarding recommended interventions for emergency departments (EDs) facing a sudden nursing shortage. Methods We queried emergency department leaders from the American College of Emergency Physicians to examine the impact of nursing shortages on EDs and to gather real-world interventions employed to mitigate the effects of the shortage. Results Most respondents (98.5%) reported nursing shortages, with 83.3% describing prolonged shortages lasting more than 12 months, with negative impacts such as misses/near-misses (93.9%) and increasing left without being seen rates (90.9%). ED leaders reported a range of interventions, including operational flow changes, utilizing alternative staff to fill nurse roles, recruitment of new nurses, and retention strategies for existing nurses. They employed temporary and permanent pay increases as well as efforts to improve the ED work environment and techniques to hire new nurses from atypical pipelines. Conclusion We report a patchwork of solutions ED leaders utilized which may have variable efficacy among different EDs; personalization is essential when selecting interventions during a sudden nursing shortage.